Optimization of Formulation and Processing Technology of Chicken Meat Spread : 10.5958/2581-6616.2020.00020.1 - Khanam, Tanveer; Goswami, Meena; Pathak, Vikas; Bharti , S.K.; Karunakara , K.N. (Journal of Meat Science, 2020)
The present work was designed to optimize the formulation and processing technology for development of chicken meat spread. Several preliminary trails were carried out to standardize the formulation of chicken meat spread. Next experiment was done to optimize the processing technology of chicken meat spread in terms of three different cooking methods viz. braising, microwave and steam cooking without pressure for different time periods. Three treatments, each selected from one cooking method were compared on the basis of various physico-chemical and sensory attributes to have one best cooking method. pH, cooking yield and moisture content of steam cooking without pressure (S) were significantly (P<0.05) higher than braising (B) and microwave (M) cooking. M and B had significantly (P<0.05) higher fat and ash contents respectively. There was no significant difference in protein content and yellowness value, however redness and lightness values showed significant (P<0.05) difference among the treatments. Among the sensory attributes, spreadability scores were significantly (P<0.05) higher in S, however flavor, meat flavor intensity and overall acceptability scores of B were significantly (P<0.05) higher than S and M. Therefore, it might be concluded that well accepted chicken meat spread might be prepared by braising cooking method for 15 minutes.